Nitrous oxide‐related neurological disorders: Clinical, laboratory, neuroimaging, and electrophysiological findings. Issue 12 (10th November 2021) - Jiang, Jiwei; Shang, Xiuli; Wang, Xiaoting; Chen, Hanze; Li, Wenyi; Wang, Yanli; Xu, Jun
Abstract: Background: Recreational N2 O abuse is an important etiology of neurological impairment in young patients, which may easily be ignored clinically. Few current studies have investigated the characteristics or the effects experienced by its users. We aimed to explore any correlation between the clinical severity and biomarkers and spinal magnetic resonance imaging (MRI) abnormalities, identify independent factors associated with spinal MRI abnormalities, and ascertain factors affecting depression/anxiety in patients with N2 O‐related neurological disorders. Methods: Patients with N2 O‐related neurological disorders were enrolled retrospectively between February 2017 and July 2020. Their demographic, clinical, laboratory, neuroimaging, electrophysiological, and neuropsychological findings were analyzed. Correlation analyses were conducted using Spearman's or Pearson's correlation and linear regression analysis. Independent factors associated with spinal MRI abnormalities were identified using univariate and multivariate analyses. Results: The principal clinical manifestations of N2 O‐related neurological disorders ( n = 63; 38 men, 25 women; mean age ± SD: 22.60 ± 4.46 years) were sensory disturbance, followed by gait disturbance and pyramidal tract damage. A significant negative correlation existed between serum vitamin B12 levels and clinical severity ( r = −0.309, p = .014), which disappeared after linear regression. An interval of less than 6 months between initial N2 O abuse and hospitalization was independently associated with spinal MRI abnormalities (39.47% vs. 72.00%, respectively; χ 2 = 6.40, p = .01). Thirty‐eight (60.32%) and 40 (63.49%) patients experienced anxiety and depression, respectively. Moreover, the higher the clinical scores/serum homocysteine levels, the greater the severity of anxiety/depression ( r = 0.442, p < .01; r = 0.346, p < .01; r = 0.477, p < .01; r = 0.324, p < .01). Conclusions: The significant inverse correlation between initial vitamin B12 levels and clinical severity could aid prognosis prediction in patients with N2 O‐related neurological disorders. Spinal MRI abnormalities were not related to clinical severity but depended on the time interval between initial N2 O abuse and hospitalization. Anxiety and depression were common comorbidity in these patients, and their severity increased with the intensity of clinical impairment and/or serum homocysteine levels. Abstract : We develop a research to explore any correlation between clinical severity and biomarkers and spinal magnetic resonance imaging (MRI) abnormalities, identify independent factors associated with spinal‐MRI abnormalities, and ascertain factors affecting depression/anxiety in patients with N2O‐related neurological disorders.